2011
DOI: 10.1088/0031-9155/56/4/017
|View full text |Cite
|
Sign up to set email alerts
|

In vivostudy of myocardial elastography under graded ischemia conditions

Abstract: The capability of currently available echocardiography-based strain estimation techniques to fully map myocardial abnormality at early stages of myocardial ischemia is yet to be investigated. In this study, myocardial elastography (ME), a radio-frequency (RF)-based strain imaging technique that maps the full 2D transmural angle-independent strain tensor in standard echocardiographic views at both high spatial and temporal resolution is presented. The objectives were to (1) evaluate the performance of ME on map… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(31 citation statements)
references
References 40 publications
2
29
0
Order By: Relevance
“…Performing speckle tracking on the raw RF signal allows for the incorporation of phase information for improved tracking in the axial direction [11] over B-mode tracking. Lee et al have shown that RF-based speckle tracking provides accurate strain measurements when compared to tagged MR in 2D myocardial slices [12], [13]. They went on to show that 2D RF-based speckle tracking could be used to identify regions of abnormal cardiac function [14].…”
Section: Introductionmentioning
confidence: 99%
“…Performing speckle tracking on the raw RF signal allows for the incorporation of phase information for improved tracking in the axial direction [11] over B-mode tracking. Lee et al have shown that RF-based speckle tracking provides accurate strain measurements when compared to tagged MR in 2D myocardial slices [12], [13]. They went on to show that 2D RF-based speckle tracking could be used to identify regions of abnormal cardiac function [14].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, if the axial direction is mainly aligned with the radial direction, positive strain will be obtained whereas negative strain will be obtained if the axial direction is mainly aligned with the circumferential or longitudinal direction. It has to be noted that angle-independency can be achieved by estimating the lateral displacement and strain and therefore derive the angle-independent radial and circumferential strain [29]. However, this goes beyond the scope of this study.…”
Section: Discussionmentioning
confidence: 99%
“…It has recently been reported that LA strain can predict the success of AF ablation [26-28]. Previous studies have shown that strains could be obtained with ME at a high frame rate and a large field of view of the heart [29]. High frame rate ultrasound imaging can be achieved with techniques such as composite imaging [30] or parallel beamforming using plane wave [31] or diverging beams [32, 33].…”
Section: Introductionmentioning
confidence: 99%
“…Radial strains were derived from the axial and lateral strains with the origin of the polar coordinate system at the centroid of the segmented myocardium. Previous studies have found that end-systolic radial strain was able to differentiate a reperfused from a normal myocardium (Lee, et al 2008) and to characterize early onset of ischemia (Lee, et al 2011). In this study, for each patient, the end-systolic radial strain was averaged in the entire cross-section of the myocardium in the short-axis view.…”
Section: Methodsmentioning
confidence: 99%
“…This technique has been validated against tagged magnetic resonance imaging and was shown to be able to differentiate normal from reperfused myocardium (Lee, et al 2008). A more recent study has shown that ME was capable of detecting, identifying and characterizing down to 40% blood flow reduction in the left anterior descending artery (LAD) of a canine model in vivo (Lee, et al 2011). In these previous studies, high frame rates were achieved while keeping a high beam density by using ECG-gating to assemble small sectors of RF signals acquired at different heartbeats into a full echocardiographic view.…”
Section: Introductionmentioning
confidence: 99%